2010
DOI: 10.1186/1472-6882-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia (bitter melon) inhibits primary human adipocyte differentiation by modulating adipogenic genes

Abstract: BackgroundEscalating trends of obesity and associated type 2 diabetes (T2D) has prompted an increase in the use of alternative and complementary functional foods. Momordica charantia or bitter melon (BM) that is traditionally used to treat diabetes and complications has been demonstrated to alleviate hyperglycemia as well as reduce adiposity in rodents. However, its effects on human adipocytes remain unknown. The objective of our study was to investigate the effects of BM juice (BMJ) on lipid accumulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…Momordica charantia, the most popularly used plant among English-speaking Afro-Caribbean diabetics, is also used in traditional Chinese and Indian medicine to treat the disease [37,38]. Recent studies indicate that Momordica charantia might help control glucose levels [39,40]. In this study, participants complained about the bitter taste of Momordica charantia and other traditional Caribbean medicines.…”
Section: Resultsmentioning
confidence: 83%
“…Momordica charantia, the most popularly used plant among English-speaking Afro-Caribbean diabetics, is also used in traditional Chinese and Indian medicine to treat the disease [37,38]. Recent studies indicate that Momordica charantia might help control glucose levels [39,40]. In this study, participants complained about the bitter taste of Momordica charantia and other traditional Caribbean medicines.…”
Section: Resultsmentioning
confidence: 83%
“…charantia and its various extracts and components are believed to exert their hypoglycemic effects via different physiological, pharmacological and biochemical modes [62][63][64] . The possible modes of the hypoglycemic actions of M. charantia and its various extracts and compounds are its hypoglycemic effect [67,70] , stimulation of peripheral and skeletal muscle glucose utilisation [71,72] , inhibition of intestinal glucose uptake [73][74][75] , inhibition of adipocyte differentiation [76] , suppression of key gluconeogenic enzymes [77,78] , stimulation of key enzyme of HMP pathway [77] , and preservation of islet β cells and their functions [66] . Today, over 140 different studies worldwide have investigated anti-hyperglycemic and hypoglycemic effects of the different extracts and ingredients of M. charantia in both human and animal models [32,33,62] .…”
Section: Possible Modes Of Action Of M Charantia and Its Extractmentioning
confidence: 99%
“…They also found that both water and ethanol extracts were effective in reducing the stable radical DPPH to the yellow colored diphenylpicryl hydrazine. The folk medicinal properties associated with bitter gourd includes treatment for various chronic and degenerative diseases, including, diabetes mellitus (Nerurkar et al, 2006;Aboa et al, 2008;Nerurkar et al, 2010) coronary heart disease and cancer (Slater, 1984;Cheng et al, 2003). The seeds of bitter gourd are believed to contain anticancer agents and remedies for gastrointestinal diseases (Beloin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%